Taxonomic studies on Begonia (Begoniaceae) in Myanmar Ⅳ: a new species, two new records, and two lectotypifications - Maw, Mya Bhone; Paing, Chit Soe; Yu, Wen-Bin (Phytotaxa, 2025)
Begonia hpaanensis, a new species from Kayin State, Myanmar, is described and illustrated herein. Based on its diagnostic morphological traits, including tuberous habit, subsymmetric leaves, a bilocular ovary with axillary placentation, two placental branches per locule, and bifid styles, this new species is placed in Begonia sect. Lauchea (Klotzsch) A.DC. Furthermore, two species are newly recorded in Myanmar and documented herein: B. saxifragifolia Craib (sect. Diploclinium (Lindl.) A.DC.) and B. phutthaii M.Hughes (sect. Apterobegonia Warb.). In addition, lectotypes are formally designated for B. adenopoda Lem. (sect. Lauchea) and B. saxifragifolia as part of this taxonomic study.